Effort required for sustained management of non‐native shrubs drops dramatically over time in a deciduous forest - David M. Jenkins; Jessica Miller Mecaskey; Chad Knisely; Rebecca M. Swab; Katharine L. Stuble (Ecological Solutions and Evidence, 2025)
Abstract Non‐native plants are a major obstacle in the restoration and management of eastern North American forests. Non‐native species, particularly woody shrubs, can be difficult to remove and are extremely persistent, thus consuming much of the time and resources available to managers. Continued, annual control effort is needed to keep non‐native abundances low. However, how that effort will vary over time is not well documented. We conducted a landscape scale experiment in which we managed non‐native shrubs over 5 years, modelling person‐hours dedicated to removing non‐native shrubs through time as a function of initial (pre‐management) non‐native shrub abundance over time. Management reduced (but did not eliminate) non‐native shrubs within the forest, and time spent controlling these shrubs dropped following the first year of management. Control efforts were strongly associated with the initial invasion level of the site in the first 2 years of management, but were unrelated to initial invasion levels thereafter. Practical implication. Our results indicate that yearly control of non‐native shrubs can maintain these undesired species at low abundances and further, that the time required for management decreases markedly after the first year. More heavily invaded forests can be expected to take more time to manage, but only over the first 2 years of management, after which management efforts are no longer contingent on pre‐management invasion levels. These results are encouraging for forest managers who seek to control non‐native shrubs within forested systems.